Economic planning and authoritarianism in the “Argentine Revolution” (1966-1971) (Quinto Sol, 2018)
The authoritarian regimes that expanded throughout Latin America in the 1960s were designed by their inspirations not only to solve the dilemmas that came from political conflict but also from the economic bottlenecks that hindered national and regional development. This article investigates how planning was specifically implemented by the regime of the “Argentine Revolution,” since its inception in 1966, as part of its model of authoritarian modernization. The Cordobazo showed that the authoritarian project had weaker bases than those assumed by its leaders. This determined that the planning bias was accentuated. The development plans were then conceived as a public action mechanism with a strong techno-bureaucratic content with the expectation that a national capitalism could be established. But they were also planned as a mechanism for expanding the social base of support, vis à vis the transition that was approaching.
Keywords: economic development; planning; authoritarianism; political transition